2019
DOI: 10.1111/issr.12212
|View full text |Cite
|
Sign up to set email alerts
|

Social protection systems and the future of work: Ensuring social security for digital platform workers

Abstract: Digitalization is transforming societies and economies worldwide at an unprecedented scale and pace. In the wake of automation and digitalization, new forms of employment have been emerging in various occupations and sectors, such as the digital platform economy. The emergence of new forms of employment, such as work on digital platforms, requires that existing social protection systems adapt to the specific situation and needs of such workers, as to realize the human right to social security for all. Current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 16 publications
1
69
0
7
Order By: Relevance
“…Renewed public and political awareness of the importance of social protection emphasizes that adequate social protection and health care should be available to all, throughout their lives, in order to manage labour market and life‐cycle risks as well as shocks, such as health pandemics. This should include workers in all forms of employment, including the self‐employed and those in “new” forms of employment (ILO, forthcoming (a); Behrendt et al, 2019). In a similar fashion to the revalorisation of social protection, there have been positive perception shifts in the world of work too.…”
Section: Can the Crisis‐induced Social Protection Response Repair Thementioning
confidence: 99%
See 1 more Smart Citation
“…Renewed public and political awareness of the importance of social protection emphasizes that adequate social protection and health care should be available to all, throughout their lives, in order to manage labour market and life‐cycle risks as well as shocks, such as health pandemics. This should include workers in all forms of employment, including the self‐employed and those in “new” forms of employment (ILO, forthcoming (a); Behrendt et al, 2019). In a similar fashion to the revalorisation of social protection, there have been positive perception shifts in the world of work too.…”
Section: Can the Crisis‐induced Social Protection Response Repair Thementioning
confidence: 99%
“…The COVID‐19 crisis has confirmed that the need for social protection is universal, reinforcing the call for universal social protection systems, including floors. The crisis has shown that accelerated effort is required in particular to extend social protection to those who are not yet or inadequately covered, including workers (and their dependants) in “non‐standard” forms of employment, self‐employment and “new” forms of employment (Behrendt et al, 2019; ILO, 2016a and 2019b; OECD and ILO, 2019). Enshrining programmes in national legislation can overcome the limitations of ad hoc and fragmented approaches, and ensure their sustainability and inclusiveness.…”
Section: Policy Considerations and Recommendations To Pave A High‐roamentioning
confidence: 99%
“…In recent years, we have seen discussions on the change on the labour market as a consequence of new technology (Greve, 2017) and the situation of those working on platforms. The latter are self‐employed and therefore typically been considered outside the scope of the welfare states (Behrendt, Nguyen, & Rani, 2019; Hill, 2015). Thus, the COVID‐19 crisis might even have been a first step in that a new group might be better covered in the years to come.…”
Section: Resultsmentioning
confidence: 99%
“…While the debates on labour market changes due to processes of flexibilization and technological changes are rather well established in economic, political, and social fields (Emmenegger et al, 2012;Goos et al, 2014), the recent changes in work arrangements, accompanied by the progressive spread of digital labour platforms, are posing new challenges to the analysis of contemporary work, economies, and societies (Behrendt et al, 2019;Kurer & Palier, 2019;Meyer, 2019). In this context, public statistics are also struggling to represent and monitor these changes.…”
Section: Introductionmentioning
confidence: 99%